Performance assessment of a private finance initiative road project - Akbıyıklı, Rıfat (Transport, 2013)
Private Finance Initiative (PFI) projects are designed to fund long-term infrastructure projects and public services. A typical PFI road scheme involves the public sector client (Granting Authority), the private sector partner – Special Purpose Vehicle (SPV), the financial lenders, the road constructor and its supply chain, technical advisers (legal, financial, technical) and the operation and maintenance (O&M) company. The O&M period is the longest phase of a PFI road project and shall be carried out in accordance with the requirement of the Project Agreement (PA); in accordance with all statutory requirements and Environmental Statements; in accordance with the road project's Quality Plan; and in accordance with Good Industry Practice in order to satisfy the Granting Authority Requirements. The concession period of the study project is 30 years. It is the most important phase because during this time both the service details and payment is created. The payment of the unitary fee is conditional on the SPV meeting certain ‘performance’ and ‘availability’ requirements set out in the PFI contract. The fee can be reduced if these standards are not met. This practice of ‘deductive payments’ and ‘non-performance’ is one of the main justifications for PFI which is described by the UK government as transferring O&M risks to the private sector in a PFI road project. This paper reports the operational performance assessment for a PFI road project in Scotland–UK detailing physical and functional performance as the critical O&M criteria. The paper also discusses the findings in the case study which are based on a longitudinal Customer Satisfaction Survey conducted between 2005–2009 years. Also, this study has proposed a conceptual framework for the O&M management practice in PFI road projects in the UK, based upon a single empirical case study and the four years longitudinal study.First Published Online: 03 Apr 2013